Diverse Anti-Tumor Immune Potential Driven by Individual IFNα Subtypes - Buzzai, Anthony C.; Wagner, Teagan; Audsley, Katherine M.; Newnes, Hannah V.; Barrett, Lucy W.; Barnes, Samantha; Wylie, Ben C.; Stone, Shane; McDonnell, Alison; Fear, Vanessa S.; Foley, Bree; Waithman, Jason (Frontiers in Immunology, 2020)
Immunotherapies harnessing T cell immunity have shown remarkable clinical success for the management of cancer. However, only a proportion of patients benefit from these treatments. The presence of type I interferon (IFN) within the tumor microenvironment is critical for driving effective tumor-specific T cell immunity. Individuals can produce 12 distinct subtypes of IFNα, which all signal through a common receptor. Despite reported differences in anti-viral potencies, the concept that distinct IFNα subtypes can improve anti-cancer treatments remains unclear. We tested whether expression of unique IFNα subtypes confined to the tumor microenvironment enhances tumor control. This was systematically evaluated by transplantation of B16 murine melanoma cells secreting five unique IFNα subtypes (B16_IFNα2; B16_IFNα4; B16_IFNα5; B16_IFNα6; B16_IFNα9) into a pre-clinical murine model. We show that IFNα2 and IFNα9 are the only subtypes capable of completely controlling tumor outgrowth, with this protection dependent on the presence of an adaptive immune response. We next determined whether these differences extended to other model systems and found that the adoptive transfer of tumor-specific CD8+ T cells engineered to secrete IFNα9 delays tumor growth significantly and improves survival, whereas no enhanced survival was observed using T cells secreting IFNα4. Overall, our data shows that the expression of distinct IFNα subtypes within the tumor microenvironment results in different anti-tumor activities, and differentially affects the efficacy of a cancer therapy targeting established disease.